Web evolutionary dynamics - Kononova, Kateryna Yuryevna (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
Nonlinear dynamic model has been suggested for assessing and predicting the number of social network users. It was shown that Maurer and Huberman’s model describes the dynamics of users quite well in the short term. But the appearance of new services and changes in network strategy shift the parameters of system, which significantly affects to users’ dynamics in the long-term. So the objective of the study was the modeling of the number of social network users in the long-term. The results have shown that the introduction of variable coefficients allows to describe the dynamics of real data more qualitative – the system can have several stable states of equilibrium; dynamics depends on the competitors’ strategies; the final state of the system is sensitive to initial conditions.